Gemcitabine combination therapies induce apoptosis in uterine carcinosarcoma patient-derived organoids - Dahl, Matías J.; Lofgren, Kristopher A.; Haugen, Cleo; Harmon, Gil E.; Hughes, Sarah P.; Cowden Dahl, Karen D. (Frontiers in Oncology, 2024)
Uterine carcinosarcoma (UCS) is a rare but aggressive endometrial cancer. Survival outcomes for women diagnosed with UCS remain poor with lower survival than those of endometrioid or high-grade serous uterine cancers. The histopathological hallmark of carcinosarcoma is the presence of both sarcomatous and carcinomatous elements. The survival rates for UCS have not improved for over 40 years; therefore, there is a profound need to identify new treatments. To investigate novel chemotherapy treatment combinations for UCS, we generated a UCS patient-derived organoid (PDO) cell line from a patient that received neoadjuvant treatment with paclitaxel and carboplatin. The PDO cell line (UCS1) was grown in three-dimensional domes. The PDO domes were treated with six individual chemotherapies or nine combinations of those six drugs. Cell death in response to chemotherapy was assessed. We found that the six monotherapies had minimal effectiveness at inducing cell death after 48 h of treatment. The combination of paclitaxel and carboplatin (which is the standard-of-care chemotherapy treatment for UCS) led to a small increase in apoptosis compared with the monotherapies. Importantly, when either carboplatin or paclitaxel was combined with gemcitabine, there was an appreciable increase in cell death. In conclusion, for the UCS1 patient-derived tumor cells, gemcitabine combinations were more effective than carboplatin/paclitaxel. Our data support the use of PDOs to predict responses to second-line chemotherapy.